Regional and teleseismic event detection capability of the small-aperture Tripoli seismic array, Greece - Pirli, M.; Schweitzer, J. (Bulletin of the Geological Society of Greece, 2007)
The Tripoli Seismic Array (TRISAR) is a small-aperture array designed to monitor and locate the seismicity in the area of Greece. In this study, its detection capabilities are discussed for regional and teleseismic events. A reference event list is compiled, consisting of events ofmb>5.0for regional and teleseismic distances (A>6°), according to the ISC On-line Bulletin. TRISAR automatically detected approximately 25% of these events over the entire investigated distance range. Although TRISAR slowness vector residuals are rather large, as expected for an array of such small aperture, the benefits resulting from the use of such a system for reporting regional and teleseismic activity is obvious.